Bifidobacterium longum alleviates irritable bowel syndrome-related visceral hypersensitivity and microbiota dysbiosis via Paneth cell regulation. Issue 1 (9th November 2020) - Zhou, Chunhua; Fang, Xue; Xu, Jiajia; Gao, Jun; Zhang, Ling; Zhao, Jiulong; Meng, Yuting; Zhou, Wei; Han, Xu; Bai, Yu; Li, Zhaoshen; Zou, Duowu
ABSTRACT: Although the oral administration of Bifidobacterium longum ( B. longum ) relieves the signs of irritable bowel syndrome (IBS) in clinical settings, the mechanisms underlying its effects are unclear. In this study, we evaluated the precise effects of B. longum on IBS via regulation of Paneth cell function. We confirmed the beneficial effects of B. longum on defecation habits and visceral hypersensitivity in WAS rats. Further analysis revealed that B. longum enhanced mucosal repair, promoted lysozyme production, and ameliorated dysbiosis of the microbiota in WAS rats. These processes are closely correlated with Paneth cell functions. In vitro, we incubated primary cultured enteroids with B. longum and found that B. longum promoted the proliferation of these organoids; this may be attributed to the upregulation of the stem niche factors WNT3A and TGF-β, which are secreted by Paneth cells. Based on our findings, we propose that B. longum relieves IBS by restoring the antimicrobial activity and stem niche maintenance function of Paneth cells.